A green miniemulsion-based synthesis of polymeric aggregation-induced emission nanoparticles1. Issue 35 (21st September 2015) - Cao, Zhihai; Xu, Chang; Liang, Lihua; Zhao, Zujin; Chen, Bin; Chen, Zhijie; Chen, Hangnan; Qu, Gan; Qi, Dongming; Shan, Guorong; Ziener, Ulrich
<x xml:space="preserve">Abstract</x> A green miniemulsion-based technique for preparing polymeric aggregation-induced emission nanoparticles was described.